Penggunaan Lagu dalam Meningkatkan Kemampuan Menghafal pada Pembelajaran Matematika Siswa Kelas II Sekolah Dasar Islam Terpadu Al Azhar Galang - Nurrahma Dewi; Astria Ayu Ramadianti; Syarifah Ainun Harahap (Medan Resource Center, 2025)
This study investigates the use of children’s songs as an instructional medium to enhance memorization skills in learning mathematical place value concepts among second-grade students at Al Azhar Galang Integrated Islamic Elementary School during the 2024/2025 academic year. The research is motivated by students’ persistent difficulties in memorizing basic mathematical concepts, the limited use of engaging learning strategies, and the lack of innovative models integrating music into mathematics instruction. Grounded in educational and cognitive learning theories, songs are assumed to facilitate learning by increasing motivation, creating an enjoyable classroom atmosphere, and reinforcing memory through structured melody and rhythm. Employing a qualitative research design, this study explores students’ and teachers’ experiences in implementing song-based learning, as well as identifying contextual and pedagogical factors that influence its effectiveness. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed thematically. The findings indicate that the use of songs contributes positively to students’ memorization abilities, engagement, and conceptual understanding of place value. The study concludes that song-based learning represents a viable and innovative pedagogical approach in elementary mathematics instruction, offering both theoretical contributions to learning theory and practical implications for teachers and educational institutions.